The Standard of Education Costs Within the Allocative Function of Public Finances Sector - Kowalska, Iwona (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
The allocative function of the public finances system requires taking a new perspective on the method of calculating the value of the financial means, directed to the units of local self-government with the aim of realization of public tasks. The article makes an attempt at presenting a method of calculating the standard of education costs in Poland. The paper includes methodological indications concerning the calculation of: 1. the compulsory number of hours in respective types and kinds of schools per number of teaching posts, 2. the payroll cost of one teaching post in schools run by units of local self-government (JST). The methodological remarks concern the instutitions run by rural communes. The proposed calculation method can also be employed with regard to the institutions subordinated to other JST (urban, and rural-urban communes, districts, regional governments).

Funkcja alokacyjna systemu finansów publicznych wymaga nowego spojrzenia na sposób liczenia środków przekazywanych jednostkom samorządu terytorialnego na realizację zadań publicznych. Artykuł jest próbą zaprezentowania sposobu liczenia standardu kosztów kształcenia w Polsce. W artykule zostały zamieszczone uwagi metodologiczne w zakresie liczenia: 1. obowiązkowego wymiaru godzin w poszczególnych typach i rodzajach szkół w przeliczeniu na etaty nauczycielskie, 2. kosztów jednego etatu nauczycielskiego w szkołach prowadzonych przez jednostki samorządu terytorialnego (JST). Uwagi metodologiczne dotyczą bazy placówek, dla których organem prowadzącym są gminy wiejskie. Zaproponowaną metodologię liczenia można także zastosować w placówkach podlegających innym JST (gminy miejskie i miejsko-wiejskie, powiaty, województwa samorządowe).
Standard kosztów kształcenia w alokacyjnej funkcji sektora finansów publicznych